English Vocabulary Mastery and The Interferences Made by The Students of Sasak Learning English - Sugianto Sugianto (EDU Journal - English Department of UMMU Journal, 2022)
The article is aimed at revealing some crucial language interferences that happened to Sasak students who were learning English. The Sasak itself is a sub-Austronesian language spoken by most of the citizens who live in Lombok and half of western Sumbawa. These language interferences play very important roles either in helping the students master English or challenging them. The positive interferences brought easiness to the students of Sasak to master English vocabulary. On the other hand, the negative interferences caused difficulties for students to learn English as their second language. The article says that defining the language interferences between Sasak and English brought some positive effects, particularly since it is a real endeavor to help the lecturers, teachers, and instructors of English in conducting teaching and learning practices. The research was conducted for the sake of finding evidence of these interferences issues. The interview was conducted by involving sasak students who were learning English. Moreover, a writing test of vocabulary was also conducted to confirm the language interferences existence when producing English words. Went through the research, and it was concluded that some morphemes that exited in the Sasak were a lot similar to morphemes that existed in English. Positively, these facts brought good effects on students who were learning English. Unfortunately, the accents in pronouncing those words were completely different which then challenged the students to master the English vocabularies.